ANALISIS PENURUNAN BIAYA POKOK PENYEDIAAN TENAGA LISTRIK BELAWAN DENGAN REPOWERING PLTU BELAWAN 4X65 MW MENJADI PLTGU 500 - 600 MW - Eri Prabowo; Agung Hariyanto; Wijang Setiyo Purwoko (Sekolah Tinggi Teknik - PLN, 2018)
Belawan steam power plant has been operating since 1984 with a configuration of 4 x 65 MW. The Belawan power plant is designed to operate with Marine Fuel Oil (MFO) fuel oil. By age, the Belawan power plant has exceeded its design life (the average design life of the plant is 25 to 30 years) and has decreased its power (Derating) and efficiency. So with the condition causes the Cost of Supply Power Supply is not competitive in North Sumatra System with Levelized Tariff value of 2,485.13 (Rp / kWh). From the study of the implementation of Repowering for Belawan steam power plant with configuration per unit of 1-1-2 resulted in Plant efficiency and Heat Rate better than the configuration per unit of 1-1-1. Estimated investment cost of Repowering Belawan Power Plant Configuration 2x260 MW is US 500,680,375.63 * Rp. 13,556, - (December middle rate 2017) = Rp. 6,787,328,578,382,54 and the value of its Levelized Tariff is 1,196.22 (Rp / kWh). Repowering with configuration per unit of 1-1-2 has GT 260.949 MW / Unit output, Total Plant Output 739.32 MW, Heat Rate 6072.19 BTU / kWh and Plant efficiency 56.15%.